Watching the Clock: Action Timing, Patterning, and Routine Performance - Turner, Scott F.; Rindova, Violina P. (Academy of Management Journal, 2018)
This study contributes to research on the temporality in routines by proposing that action timing is a patterning mechanism, distinct from the sequence-based patterning that has been the focus of current research. We examine the effect of this mechanism by investigating how recurrent action timing—and its reproduction—affect the effectiveness of routine performance. We further theorize and show that multiplicity in the performative and the ostensive aspects of the routine influence the strength of timing-based patterning and its effects. We test our ideas using a unique dataset that tracks specific garbage collection actions and captures their precise timing, combined with corresponding data on customer complaints about missed collections. Our findings support our theoretical predictions and advance current understanding about different temporal patterning mechanisms in routines.